Workshop Manajemen Referensi dan Sitasi Menggunakan Mendeley pada Mahasiswa PGSD Unram - Hasnawati Hasnawati; Fitri Puji Astria; Muhammad Erfan; Hikmah Ramdhani Putri (Indonesian Publication Center, 2025)
Reference and citation management skills are essential skills in writing scientific papers. Unfortunately, many students still have not mastered the technique optimally, which has an impact on the low quality of the scientific papers they produce. This workshop was held to equip students of the Elementary School Teacher Education Study Program (PGSD) of the University of Mataram (UNRAM) with an understanding and practical skills in using the Mendeley application as a reference and citation management tool. This activity is divided into 3 stages, namely the preparation stage, the implementation stage and the evaluation stage. In the preparation stage, the research team first coordinated with partners, then conducted participant recruitment and divided the job descriptions of each team member. The implementation stage includes the presentation of the basic concept of reference and citation management, introduction to Mendeley features, simulations and trying out direct practice using the Mendeley application. Furthermore, the evaluation stage is carried out through analysis of the results of the pre-test and post-test as well as participant response questionnaires regarding the implementation of the activities that have taken place. This evaluation aims to see the extent to which the objectives of the activities carried out have been achieved. This workshop activity was carried out at campus 2 FKIP Universitas Mataram on May 27, 2023. Based on the results of the pretest and posttest, there was an increase in the understanding of students participating in the workshop regarding how to manage references using the Mendeley application and also citations. Where participants were able to apply basic features such as managing reference documents, inserting automatic citations, and compiling bibliographies. Based on the results of participant responses to the workshop activities carried out, on average students gave positive responses.